A direct access to heterobimetallic complexes by roll-over cyclometallation. Issue 88 (23rd October 2017) - Schön, F.; Leist, M.; Neuba, A.; Lang, J.; Braun, C.; Sun, Y.; Niedner-Schatteburg, G.; Bräse, S.; Thiel, W. R.
Abstract : Creation of a novel chelating site by roll-over cyclometallation opens up a new strategy for a rapid access to heterobimetallic complexes. Combinations of iridium(iii ) with palladium(ii ) or platinum(ii ) have exemplarily been synthesized. Abstract : Complexes of the type [Cp*Ir( N, N ′)Cl] + ( N, N ′ = 2-(2-dialkylaminopyrimidin-4-yl)pyrimidine) can undergo roll-over cyclometallation leading to a novel N, N ′-donor site. Following this strategy heterobimetallic complexes including iridium(iii ) and a Group X metal centre in the oxidation state +II were achieved.